Sodium caseinate increases the number of B lymphocytes in mouse - Vanihamín Domínguez; Itzen Aguiñiga; Leticia Moreno; Beatriz Torres; Edelmiro Santiago-Osorio (Biomédica, 2017)
Introduction: Sodium caseinate, a casein salt, is a proinflammatory agent in mice, and it is able to induce granulopoiesis in vivo and to increase the production of cytokines, which is key for this biological process. Objective: To assess whether sodium caseinate is able to induce a biological effect on cells from lymphoid origin and the production of cytokines involved in this lineage in vivo. Materials and methods: We used female BALB /c mice from 8 to 12 weeks old. The animals were injected intraperitoneally (IP) with 1 ml of sodium caseinate (10% PBS w/v) four times every 48 hours. The B cell populations and the incorporation of BrdU were analyzed by flow cytometry. Detection of interleukin-7 was assessed by ELISA (Enzyme-Linked ImmunoSorbent Assay). Results: We established that after intraperitoneal injection, the number of B lymphocytes 220+ from the spleen of mice treated with sodium caseinate increased compared to those that only received the vehicle (89.01±1.03 vs 75.66 ± 2.08), and the same was observed with the incorporation of BrdU in B220 + cells (38.59±4.48 vs 11.82±1.04 respectively). We also established that the concentration of interleukin-7 (IL-7) in the serum of mice treated with sodium caseinate increased compared to those that only received the vehicle (62.1 ± 17.5 vs 26.9 ± 4.4 pg/ml). Conclusion: Sodium caseinate was able to increase the number of B lymphocytes in the spleen; it also induced IL-7 production, a cytokine that is key for the B cell lymphopoiesis.